2019
DOI: 10.1002/lary.28411
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis does not support routine traditional nuclear medicine studies for malignant otitis

Abstract: Objectives The role of traditional nuclear medicine studies in the management of malignant otitis externa (MOE) is unclear and there are ongoing debates regarding their diagnostic value. The authors perform a systematic review and meta‐analysis to assess the sensitivity and specificity of traditional nuclear medicine studies in the diagnosis of MOE. Methods In accordance with PRISMA guidelines, a query of the Medline, Embase, Web of Science, and Cochrane databases was undertaken. The primary outcomes of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…This study has shown Technetium to be effective in both the diagnosis and exclusion of NOE in patients thought to have clinically evident disease but in whom the initial CT was negative. Despite recent meta‐analysis not supporting the use of nuclear imaging studies in the management of NOE, 8 this study does reveal its clinical utility to reduce unnecessary prolonged antibiotic therapy, which can be associated with prolonged hospital stay and complications. This study does however concur regarding the limitations in Gallium imaging and would not advocate its routine use.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study has shown Technetium to be effective in both the diagnosis and exclusion of NOE in patients thought to have clinically evident disease but in whom the initial CT was negative. Despite recent meta‐analysis not supporting the use of nuclear imaging studies in the management of NOE, 8 this study does reveal its clinical utility to reduce unnecessary prolonged antibiotic therapy, which can be associated with prolonged hospital stay and complications. This study does however concur regarding the limitations in Gallium imaging and would not advocate its routine use.…”
Section: Discussionmentioning
confidence: 72%
“…There remains some doubt as to the clinical utility of nuclear imaging in the management of NOE, with many centres abandoning them and a recent meta‐analysis advising their avoidance 8 . Portsmouth Hospitals University NHS Trust remains in a minority of centres still utilising the techniques, due to a relatively high local incidence and development of refined protocols over years.…”
Section: Introductionmentioning
confidence: 99%
“…1,11,36 Overall, the literature has variable data regarding the overall diagnostic value of nuclear medicine studies. 37 A recent review of malignant otitis externa literature revealed pooled sensitivities for technetium-99 and gallium-67 of 85.1% and 71.2%, respectively, with poor specificity; however, the data were deemed insufficient for a meta-analysis. The authors, therefore, advised against the routine use of these studies in SBO management in patients with a known diagnosis on conventional imaging.…”
Section: Pathologymentioning
confidence: 99%
“…However, these examinations were considered to be reasonably sensitive tests in patients with an unclear diagnosis despite an otomicroscopic examination or other imaging studies. 37 The authors also concluded that there were insufficient data to determine the usefulness of these modalities during followup and that larger prospective studies would be necessary.…”
Section: Pathologymentioning
confidence: 99%
“…The utility of Tc99m and Ga67 studies as the standard for the diagnosis and monitoring of MOE has recently been drawn into question. Moss et al 3 conducted a systematic review and meta-analysis of 20 studies that evaluated the accuracy of Tc99m and Ga67 in the diagnosis and assessment of treatment response in MOE. Their analysis of 608 patients reported pooled sensitivities for Tc99m and Ga67 of 85% (95% CI, 72-98.1%) and 71.2% (95% CI, 55.1-87.3%), respectively.…”
Section: Literature Reviewmentioning
confidence: 99%